PENGARUH PENDAPATAN DAN LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN DENGAN GAYA HIDUP SEBAGAI VARIABEL PEMODERASI - Ali, Mujahid Zaid; Asyik, Nur Fadjrih (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
Financial behavior has an important role in this latest situation within the organization and company, and also in employees. The main issue is lack of understanding of financial behavior. Therefore, it is important to find out how lifestyle can affect someone’s financial behavior in self-controlling. This research aimed to examine the effect of income and financial literacy on financial behavior, with lifestyle as a moderating variable. The research was quantitative. Moreover, the population was 156 employees who worked at Sarana Metal Group Surabaya. The data collection technique used purposive sampling, which the sample was based on the criteria given. In line with that, there were 54 respondents as the sample. Furthermore, the data analysis technique used Moderated Regression Analysis (MRA) with SPSS 23. The result concluded that 1) income had a positive effect on financial behavior; 2) financial literacy had a positive effect on financial behavior; 3) lifestyle could not be able to moderate the effect of income on financial behavior; and 4) lifestyle could moderate the effect of financial literacy on financial behavior at Sarana Metal Group Surabaya.